Aberrant activation of the type I interferon system may contribute to the pathogenesis of anti‐melanoma differentiation‐associated gene 5 dermatomyositis. (1st May 2019) - Zhang, S.H.; Zhao, Y.; Xie, Q.B.; Jiang, Y.; Wu, Y.K.; Yan, B.
Summary: Background: Anti‐melanoma differentiation‐associated gene 5 (MDA5) dermatomyositis (DM) is a distinctive subtype of DM that carries a significant risk of interstitial lung disease (ILD). The mechanisms remain elusive. Objectives: To explore the role of the type I interferon (IFN) system in the pathogenesis of anti‐MDA5 DM. Methods: Twenty patients with anti‐MDA5 DM were studied and compared with patients with anti‐aminoacyl‐tRNA synthetase (ARS) DM ( n = 10) and autoantibody‐negative patients with DM ( n = 20). The levels of inflammatory cytokines, B‐cell‐activating factor (BAFF) and Krebs von den Lungen (KL)‐6 in blood were tested by enzyme‐linked immunosorbent assay and multiplex assays. Expressions of transcripts for IFN‐associated sensors and type I IFN‐inducible genes in peripheral blood mononuclear cells (PBMCs) were detected by real‐time polymerase chain reaction. Expressions of the signal transducer and activator of transcription (STAT)1, interferon‐stimulated gene (ISG)15 and MxA proteins in skin lesions were analysed by immunohistochemistry. Results: Plasma IFN‐α levels were significantly increased in patients with anti‐MDA5 DM. PBMCs from patients with anti‐MDA5 DM showed significant upregulation of the TLR3, TLR7, IFIH1 and DDX58 genes, as well as serial IFN‐inducible genes. Skin biopsies from patients with anti‐MDA5 DM were characterized by strong expression of the STAT1, ISG15 and MxA proteins. In the patients with anti‐MDA5 DM and ILD with high IFN‐α production, there was a positive quantitative correlation between IFN‐α and BAFF ( r s = 0·63, P = 0·044). In addition, the higher levels of BAFF paralleled the higher concentrations of KL‐6 ( r s = 0·86, P = 0·0012). Conclusions: Our data confirm the aberrant activation of the type I IFN system in anti‐MDA5 DM. Overproduction of IFN‐α linked with BAFF may be implicated in the development of ILD.